2013
DOI: 10.1089/scd.2013.0142
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Systemic Administration of Human Adipose-Derived Stem Cells Attenuates Overt Diabetic Nephropathy in Rats

Abstract: Adipose-derived stem cells (ASCs) can alleviate acute kidney injury and promote kidney cell regeneration and repair. To investigate the role of ASCs in diabetic nephropathy (DN), Sprague-Dawley rats were made diabetic by intraperitoneal injection of streptozotocin (STZ) after uninephrectomy. After 12 weeks, proteinuria was well established. Five times of 5 · 10 6 human ASCs repeatedly injected through a tail vein at 4 weekly intervals. A reduction in proteinuria was not observed in diabetic rats until 24 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…Increased survival, improved renal function, and increased levels of chemoattractants by pFUS during early AKI or clinically established AKI suggest that therapies using pFUS and MSC may be possible during subacute or chronic phases of pathology. pFUS induction of a transient molecular zip‐code might allow multiple courses of cell therapy, a regenerative medicine approach with some promise , that is analogous to metronomic anticancer therapy. Extending the oncological analogy, pFUS can be further characterized as a neoadjuvant approach for infused cell therapies by altering the targeted microenvironment to induce an EHPR effect and improve functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased survival, improved renal function, and increased levels of chemoattractants by pFUS during early AKI or clinically established AKI suggest that therapies using pFUS and MSC may be possible during subacute or chronic phases of pathology. pFUS induction of a transient molecular zip‐code might allow multiple courses of cell therapy, a regenerative medicine approach with some promise , that is analogous to metronomic anticancer therapy. Extending the oncological analogy, pFUS can be further characterized as a neoadjuvant approach for infused cell therapies by altering the targeted microenvironment to induce an EHPR effect and improve functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that single administrations of allogeneic MSCs are safe and potentially effective in ischemic heart disease [30]. Preclinical studies have shown that in CKD, repeated injections are often required to ameliorate disease progression [31,32], which may increase the likelihood of sensitization which is less desirable in patients likely to require a kidney transplant. Autologous MSCs may thus be preferable for these patients, provided there is limited disease-related dysfunction as we have demonstrated in the present study.…”
mentioning
confidence: 99%
“…There is evidence that exosomes may be able to aid in the treatment of diabetic nephropathy. Studies have found that stem cells have a reparative effect on renal tissues in both diabetic nephropathy and other kidney diseases (Zhang et al 2013). As previously discussed, the paracrine signaling effect of exosomes may aid in stem cell-mediated regenerative processes, including the repair of renal tissue.…”
Section: Stem Cell-derived Exosomes Can Regenerate Tissue Damage Frommentioning
confidence: 91%